2022
DOI: 10.3389/fcvm.2022.850223
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Heart Rate Variability Is Positively Associated With the Risk of Adverse Cardiovascular Outcomes

Abstract: IntroductionPrevious studies found visit-to-visit heart rate variability (VVHRV) may be positively associated with risks of several cardiovascular events, but whether VVHRV affected the benefit of intensive blood pressure control remained unknown. In this study, we assessed the risk of the composite cardiovascular outcomes associated with VVHRV among the older patients with hypertension and evaluated whether the benefit of intensive blood pressure control in the prevention of the composite cardiovascular outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…The influence of long-term HRV, which refers to variation over months or years, on the prognosis of patients with AF is rarely reported. Prior investigations have shown that VVHRV is linked to various adverse cardiovascular events (Zeng et al, 2022), including new-onset AF (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of long-term HRV, which refers to variation over months or years, on the prognosis of patients with AF is rarely reported. Prior investigations have shown that VVHRV is linked to various adverse cardiovascular events (Zeng et al, 2022), including new-onset AF (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of long‐term HRV, which refers to variation over months or years, on the prognosis of patients with AF is rarely reported. Prior investigations have shown that VVHRV is linked to various adverse cardiovascular events (Zeng et al., 2022 ), including new‐onset AF (Zhang et al., 2021 ). The analysis (Zhang et al., 2021 ) based on data from the Kailuan study cohort suggested that both higher and lower VVHRV levels might elevate the risk of new‐onset AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Moreover, the visit-to-visit heart rate variability (VVV-HR) has been demonstrated to be more important than only using single time point heart rate data in relation to future risk of adverse clinical events. 15 Also, high heart rates may lead to increased oxygen demands that could contribute to adverse clinical outcome, 16 including with new-onset AF. 17 As far as we are aware, the relation of VVV-HR to adverse clinical outcomes in patients with AF has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Also, visit‐to‐visit heart rate variability (HRV) is associated with higher cardiovascular risk outside pregnancy. 4 Heart rate (HR) is routinely measured by automated BP measurement devices in pregnancy but is poorly recorded in maternity records, and it is not known whether HR is related to adverse pregnancy outcomes.…”
mentioning
confidence: 99%